2012
DOI: 10.1002/anie.201104313
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Fingerprint Analysis

Abstract: Fingerprints have been used in forensic investigations for the identification of individuals since the late 19th century. However, it is now clear that fingerprints can provide significantly more information about an individual. Here, we highlight the considerable advances in fingerprinting technology that can simultaneously provide chemical information regarding the drugs ingested and the explosives and drugs handled by a person as well as the identity of that individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
197
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(203 citation statements)
references
References 70 publications
0
197
0
6
Order By: Relevance
“…Although reviews of fingerprint research are of high quality and very detailed, they reveal a general lack of degradation product analyses in studies of fingerprint aging [39,[41][42][43]. But Mountfort et al should be named as they identified mono hydroperoxides as degradation products of squalene in solution and in fingerprints [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although reviews of fingerprint research are of high quality and very detailed, they reveal a general lack of degradation product analyses in studies of fingerprint aging [39,[41][42][43]. But Mountfort et al should be named as they identified mono hydroperoxides as degradation products of squalene in solution and in fingerprints [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances by our research group using an immuno-labelling approach based on the use of fluorescently labelled, antibody-functionalised magnetic particles have shown the detection of drug metabolites endogenously produced in the latent fingermarks of drug users [18][19][20]. In addition, Rowell et al were able to show isolated patches of cocaine contamination in a fingerprint obtained from an individual being treated at a drug addiction centre using surface assisted laser desorption/ionisation time-of-flight mass spectrometry (SALDI-TOF-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of fingerprints already deposited on surface can change with time due to a variety of factors, such as evaporation of volatile components of fingerprints, diffusion of fingerprints into porous surface, exposure to light, temperature and humidity, and many more [1,5]. Even though there are a number of optical, chemical and physical techniques available for fingerprint analysis a considerable portion of the latent fingerprints still escape detection, resulting in inaccurate analysis.…”
Section: Various Techniques Utilized For Forensic Analysis Of Fingerpmentioning
confidence: 99%
“…Owing to the fact that this pattern is unique to each individual and doesn't change throughout a person's life, it has been used as a biometric identifier by the criminologists and law enforcement officers in forensic investigations since late 19th century [1]. Apart from the scars which originated from any accidents, fingerprints remain same throughout a person's life.…”
Section: Introductionmentioning
confidence: 99%